Extraction, purification and characterization of polygalacturonase from durian (Durio zibethinus L.) seed - Asmadi, Farhana Azmira (2017)
Polygalacturonase breaks down pectin chains generally found in the cell wall of plant. Primarily, enzymes have high tendency to be degraded by improper extraction method. Therefore, it is essential to use an economical, simple and efficient extraction method. In this study, polygalacturonase (PG) was extracted from durian seed with ultrasound assisted-extraction. The effects of extraction time, ultrasound temperature, pH of buffer and solvent-to-seed ratio for optimization of the extraction were determined. The optimum combination of extraction was achieved at 30 min extraction time, 50°C temperature and 5:1 ml/g of solvent-to-seed ratio at pH 5.5. Conventional purification processes are multistep, tedious and expensive; thus, it is vital to develop an economical, highly efficient and environmental friendly process for the purification of polygalacturonase with required properties. A novel aqueous two-phase system (ATPS) process composed of surfactant and acetonitrile was employed to purify polygalacturonase from Durio zibethinus seed at laboratory scale. In this study, the effect of Tie Line Length (TLL), crude loads and pH on purification of the enzyme were investigated. The results of the ATPS process indicated polygalacturonase was partitioned in the novel method of ATPS composed of 23% (w/w) Triton X-100 and 19% (w/w) acetonitrile, at 55.6% of TLL (tie line length) crude load of 25% (w/w) at pH 6.0. It was determined that the phase components, Tie Line Length (TLL), crude loads and pH effected the polygalacturonase partitioning. This study also showed that ATPS can be used as an economical and effective method for purification of the enzyme from a novel source with potential industrial application and alternative to the conventional ATPS. Characterization of the purified polygalacturonase was done to determine the polygalacturonase stability in vary conditions. In this study, it indicated that polygalacturonase extracted from durian seed was stable with the presence of some metal ions, surfactants and oxidizing agents. The metals K+, Mg2+, Na+ and Cu2+ enhanced the polygalacturonase activity to 135.1%, 108.5%, 94.6% and 86.7% respectively. Meanwhile Zn2+, Ca2+ and Fe3+ inhibited the enzyme activity to 72.9%, 49.3% and 14.1% respectively. Polygalacturonase showed high stability towards surfactants EDTA (108.1%) and SDS (101.6%). The polygalacturonase was stable in Triton X-100 (97.7%) and Tween 80 (92.5%) meanwhile almost half of the activity was inhibited by oxidizing agent to 66.7%. Based on SDS-PAGE, the estimated molecular weight of this was 34.4 kDa. Hence, as a conclusion, the enzyme with unique characteristics could be extracted and purified from natural source. It has high potential to contribute in some industrial applications such as food and beverages, textile, paper, and other biotechnological applications.